CROATS AND CROATIA IN THE WAKE OF THE GREAT WAR. (24th October 2014) - Newman, John Paul
ABSTRACT: This article addresses the experiences of Croats and Croatia in the aftermath of the First World War, showing how the interwar Kingdom of Yugoslavia privileged the wartime sacrifice of Serbia and the Serbian army and how Croats were often depicted as the remnants of a defeated state, Austria-Hungary, and therefore less entitled to citizenship in the South Slav kingdom. It focuses on three large veteran associations: the Association of Reserve Officers and Warriors, the Union of Volunteers, and the Association of War Invalids.